Education in Prison and the Self-Stigma: Empowerment Continuum. (February 2018) - Evans, Douglas N.; Pelletier, Emily; Szkola, Jason
A criminal conviction results in consequences that extend beyond incarceration. Self-stigmatization is a negative consequence that many formerly individuals experience. It manifests in low self-esteem and personal barriers to reentry. This study explores higher education programs in prison as a moderator of self-stigma. Using qualitative interviews, this study investigated the perceptions of formerly incarcerated individuals who participated in higher education in prison in regard to the ways in which incarceration and education affected their self-stigma. Results indicate that incarceration influences self-stigma, but education enhances a sense of empowerment and motivation to resist the negative effects of self-stigma. Reducing the stigmatization of formerly incarcerated individuals is important because if they view themselves positively, it can improve their reentry and life trajectory.